Mechanical Thrombectomy for Stroke Due to Acute Basilar Artery Occlusion, a Safety and Efficacy Analysis. Issue 4 (1st April 2023) - Abbas, Rawad; Chen, Ching-Jen; Atallah, Elias; El Naamani, Kareem; Amllay, Abdelaziz; Sioutas, Georgios; Gooch, M. Reid; Herial, Nabeel A.; Jabbour, Pascal; Rosenwasser, Robert H.; Tjoumakaris, Stavropoula
Abstract : BACKGROUND: Acute basilar artery occlusion accounts for 1% of all ischemic strokes but often leads to devastating neurological injury and mortality. Many institutions still opt for best medical therapy for these patients; however, there is increasing evidence that mechanical thrombectomy (MT) for these patients leads to better outcomes. OBJECTIVE: To assess the safety and efficacy of MT for patients presenting with acute basilar artery occlusion (BAO). METHODS: This study was a retrospective chart review of a prospectively maintained database for patients with acute BAO treated with MT from January 2014 through March 2022. RESULTS: Our study included a total of 74 patients. The mean age was 62.7 years, and 55.4% were male. The most common comorbidity was hypertension (73%). The mean door to puncture time was 75 minutes, and the mean procedure time was 54 minutes. 86.5% of patients had a good modified treatment in cerebral ischemia score (≥2b). There were 4 patients who had procedural complications and 3 who had symptomatic intracerebral hemorrhage. At 90 days, 62.5% of patients had a modified Rankin Scale, 0 to 3. The mortality rate was 32.4% and 2% during hospital admission and 90 days, respectively. On univariate analysis, adjunctive angioplasty/stenting and higher presenting National Institutes of Health Stroke Scale score were associated with modified Rankin Scale 4 to 6 at 90 days ( P -value, .03 and <.001, respectively). Shorter procedure time was associated with modified treatment in cerebral ischemia score ≥ 2b ( P -value, .0015). CONCLUSION: Our findings showed that MT is safe and effective for patients presenting with acute BAO and is in conjunction with previous literature. The results from upcoming trials should hopefully establish MT as gold standard for these patients.